2019
DOI: 10.1097/pcc.0000000000002055
|View full text |Cite
|
Sign up to set email alerts
|

Severity and Mortality Predictors of Pediatric Acute Respiratory Distress Syndrome According to the Pediatric Acute Lung Injury Consensus Conference Definition

Abstract: Objectives: The objective of this study was to assess the prevalence, severity, and outcomes of pediatric acute respiratory distress syndrome in a resource-limited country. In addition, we sought to explore the predisposing factors that predicted the initial severity, a change from mild to moderate-severe severity, and mortality. Design: Retrospective study. Setting: PICU in Songklanagarind Hospital, Songkhl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…A retrospective cohort study performed by researchers at the University of Washington reported that morbidity and mortality among 146,058 patients <18 years in ICUs during 2007–2016 were 1.8 % and 20 %, respectively [ 4 ]. A study in Thailand found that mortality and morbidity of the 1738 patients <15 years in pediatric ICUs (PICUs) for 2013–2016 were as high as 7.4 % and 51.2 %, respectively [ 5 ]. Additionally, an international observational study performed in total 145 PICUs from 27 countries for 2016–2017 reported that mortality and morbidity of the 23,280 patients were 3.2 % and 17 %, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study performed by researchers at the University of Washington reported that morbidity and mortality among 146,058 patients <18 years in ICUs during 2007–2016 were 1.8 % and 20 %, respectively [ 4 ]. A study in Thailand found that mortality and morbidity of the 1738 patients <15 years in pediatric ICUs (PICUs) for 2013–2016 were as high as 7.4 % and 51.2 %, respectively [ 5 ]. Additionally, an international observational study performed in total 145 PICUs from 27 countries for 2016–2017 reported that mortality and morbidity of the 23,280 patients were 3.2 % and 17 %, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the total ion chromatogram of CEE analysis, we have totally identified 12 components (Fig. 5) from CEE, they are neochlorogenic acid (1), chlorogenic acid (2), caffeic acid (3), 1,3-dicaffeoylquinic acids (4), cynaroside (5), isochlorogenic acid C (6), isochlorogenic acid A (7), isochlorogenic acid B (8), linarin (9), luteolin (10), apigenin (11), acacetin (12). We also compared the chromatograph peaks of the mixed standard compounds and the samples of CEE (Fig.…”
Section: Bioactive Component Identification Of Ceementioning
confidence: 99%
“…In 1992, the American Thoracic Society (ATS) and the European Society of Critical Diseases (ESICM) changed ARDS (adult respiratory distress syndrome) to acute, and divided it into two parts: ALI and ARDS [3]. At the same time, the causes of ALI/ARDS were classified into two major factors: direct lung injury and indirect lung injury [4][5][6]. A large number of clinical studies have shown that Gram-negative bacilli infection is the most common cause of ALI induction and is one of the main causes of death [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric acute respiratory distress syndrome (PARDS) is associated with significant mortality [1], more so in the low middleincome countries (LMIC) [2][3][4][5]. Furthermore, mortality is proportional to the severity of ARDS; 1-15% for mild and moderate ARDS and 33% for severe ARDS [6].…”
mentioning
confidence: 99%
“…In developing countries, ARDS mortality is usually contributed by the non-pulmonary organ involvement, independent of the type of ventilation [2,3]. Of these acute kidney injury and fluid overload are a lethal combination [18,19].…”
mentioning
confidence: 99%